Evaluation of Ammonia as a Potential Marine Fuel - Lövdahl, Josefin; Magnusson, Maria (My University, 2019)
Alternative marine fuels are needed to mitigate emissions from the shipping sector in order to fulfil climate targets set by the International Maritime Organisation. This study assesses the potential of ammonia as a fuel for shipping compared to other alternative marine fuels by conducting energy systems modelling by the global energy transition (GET) model and a multi-criteria decision analysis (MCDA) with stakeholder preference taken into account. This contributes to an initial assessment of cost-effective fuel choices in the shipping sector and what marine fuel that is preferred when assessing economic, environmental, social and technical impacts with weights of criteria provided by stakeholders. Besides ammonia, the alternative marine fuels considered in this study are: liquefied natural gas (LNG), hydrogenated vegetable oil (HVO), methanol (MeOH) and hydrogen (H2). The GET model perform simulations with constraints of the atmospheric CO2 concentration that must be fulfilled by year 2100. Two scenarios of different constraints, 450 ppm and 550 ppm CO2, are conducted with results stating that the most cost-effective shipping fuels at the end of the studied time period are H2 and LNG in combination with fuel cells (FC) as propulsion technology. Ammonia is cost-effective as a shipping fuel under both constraints but only to a limited extent. In the MCDA other criteria than economic performance are introduced and the evaluation is performed by the Analytic Hierarchy Process. Eleven fuel options are included in the MCDA, combining different feedstocks, production methods and propulsion technologies; internal combustion engine (ICE) or fuel cell (FC). There are four ammonia options included representing if ammonia is produced from either electrolysis based or natural gas based hydrogen and combined with either ICEs or FCs. The MCDA results in a ranking where the most preferred fuel option is hydrogen produced by electrolysis and combined with FC. Ammonia combined with FCs also perform well and end up in 2nd and 4th place, while the ammonia options with ICEs are found in the bottom of the ranking in 9th and 11th place. The results of this thesis implies that several alternative marine fuels show potential, however further assessments are needed to draw firm conclusions about the potential of ammonia as an alternative marine fuel.
Keywords: Ammonia; Alternative Marine Fuels; Shipping sector; Global Energy Transition Model; Multi-Criteria Decision Analysis